Anesthetic Management of a Case of Hemophagocytic Lymphohistiocytosis - Shrestha, Gentle S; Gulati, Harmeet; Acharya, Binita; Poudyal, Bishesh S (Journal of Institute of Medicine Nepal, 2020)
Hemophagocytic Lymphohistiocytosis (HLH) is characterized by an overwhelming activation of histiocytes and T lymphocytes leading to fulminant hemophagocytosis and organ damage. Anesthetic management of patients with HLH is associated with challenges such as pancytopenia, hemodynamic instability and infections. In addition to sepsis, metabolic acidosis, disseminated intravascular coagulation, multi-organ involvement with an exacerbation of symptoms with the use of anesthetic agents poses significant risk perioperatively. We present a case planned for excision of pilonidal sinus. The surgery was performed after thorough workup and with the patient in remission. Elective procedures should ideally be performed with patients in remission. Cases receiving concurrent therapy with immunomodulators and steroids require special attention due to possible interaction with anesthetic agents and the need for perioperative steroid supplementation.